Sobrevivencia del agente causal de la moniliasis (Moniliophthora roreri) en almendras de cacao durante el proceso de postcosecha. - Tigselema Ramírez, Jenniffer Alexandra (2019)
The moniliasis caused by the fungus M. roreri is one of the diseases that has the greatest economic impact and causes great losses, causing damage to the fruits of cocoa. There is the fear that the movement of material with or without post-harvest processes may transmit M. roreri. Although there are many studies on cocoa postharvest processes, no specific references are found regarding the risk that could exist in moving these cocoa masses to sites free of this disease. The objective of this study is to establish the growth and survival of the causal agent of moniliasis in cocoa almonds. For the present investigation the completely randomized design (CRD) was applied, and it was carried out in two phases, the first consisted of a laboratory state to evaluate the behavior of M. roreri in different temperature conditions and was carried out in the laboratory of Microbiology and Molecular Biology of the State Technical University of Quevedo (UTEQ), located in the "Manuel Haz Álvarez" University Campus located at km 1.5 via Quevedo-Santo Domingo. The second phase took place at the facilities of La Nueva Casa Del Cacao SA, Ecuadorian cocoa exporter ¨CASACAO¨ located at Km 2 ½ Vía Valencia, to evaluate the behavior of the organism during fermentation and the drying process. A descriptive analysis was made due to the results obtained from the three experiments in which M. roreri did not grow or develop at high temperatures or during the postharvest process, concluding that M. roreri does not survive at temperatures above 30 ° C in laboratory conditions. M. roreri did not survive the fermentation process, applying the method of incorporating colonies of the fungus into a micro fermentation process. It was not possible to isolate M. roreri from almonds in the process of natural (cement-based) drying or artificial drying, with humidity levels below 55%. Keywords: Moniliasis, micro Fermentation, temperatures.